The traveler's tricks : a Caroline mystery - Calkhoven, Laurie (American Girl, 2014)
On a three-day stagecoach ride to the big city of Albany, during the War of 1812, eleven-year-old Caroline is fascinated by the other travelers, including a charming magician and a beautiful young woman with a sad past, but when Caroline's important package for her father disappears, she must unmask a thief.